Ethics in Ethnobotanical Research: Intersection of Indigenous and Scientific Knowledge Systems - Alfred Maroyi, (Journal of Pharmacy and Nutrition Sciences, 2020)
This study examines the state of research ethics and professional conduct in ethnobotanical studies. In this study, “ethnobotany” is defined as the study of the knowledge, skills and daily uses of plants in a particular area that enable the people of the local community to get the most out of their environment. Ethnobotanical research impinges on local peoples’ lives, sources of livelihoods, their environment and cultures, and this raises many ethical issues in the process. This paper documented information on important ethical considerations when engaging in ethnobotanical research and discusses the importance of a written agreement with local people specifying the elements of research collaboration, the responsibilities of each party, potential benefits to be derived from the research project, intellectual property agreements and disposition of the research results.